2014
DOI: 10.1137/130947337
|View full text |Cite
|
Sign up to set email alerts
|

Smooth Hamiltonian Systems with Soft Impacts

Abstract: In a Hamiltonian system with impacts (or "billiard with potential"), a point particle moves about the interior of a bounded domain according to a background potential and undergoes elastic collisions at the boundaries. When the background potential is identically zero, this is the hard-wall billiard model. Previous results on smooth billiard models (where the hard-wall boundary is replaced by a steep smooth billiard-like potential) have clarified how a smooth billiard may be rigorously approximated using a har… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 10 publications
(58 reference statements)
0
26
0
Order By: Relevance
“…The main result here is that under some specific conditions, in a large (O(1) measure) phase space region, smooth nearintegrable dynamics are realized for sufficiently small r and w . Moreover, using [17], it is shown that these results may be extended for the smooth system in which the hard wall is replaced by a soft steep potential, provided the potential is sufficiently steep (notably, the steeper the potential is the larger the perturbation is in the C r+1 topology).…”
Section: Introductionmentioning
confidence: 94%
See 4 more Smart Citations
“…The main result here is that under some specific conditions, in a large (O(1) measure) phase space region, smooth nearintegrable dynamics are realized for sufficiently small r and w . Moreover, using [17], it is shown that these results may be extended for the smooth system in which the hard wall is replaced by a soft steep potential, provided the potential is sufficiently steep (notably, the steeper the potential is the larger the perturbation is in the C r+1 topology).…”
Section: Introductionmentioning
confidence: 94%
“…For physical setups in which bodies at close range experience strong repulsion forces (e.g. the repelling forces between two colliding atoms) [27,30,20,17], a better model for the strong repulsion than the singular hard-wall billiard potential is a smooth steep potential. Hence, consider Hamiltonian systems similar to those discussed above, where the hard billiard is replaced by a smooth potential whose softness is controlled by a small parameter b :…”
Section: Soft Impactsmentioning
confidence: 99%
See 3 more Smart Citations